COGNITION AND EXPRESSION OF SPACE IN VIETNAMESE AND CHINESE – INFLUENCES ON VIETNAMESE STUDENTS (Journal of Foreign Language Studies, 2024)
Due to its objective existence, the expression of space requires linguistic encoding, which involves the human cognition of space. Therefore, there is subjectivity and cultural specificity in the representation of space in different languages. To express spatial relationships, similar elements of expressions were used in Vietnamese and Chinese, however, there are differences in the order of those elements (grammar) and the conceptualization of space (logic-semantic). Without proper awareness and analysis of such differences, Vietnamese students can make some errors at the early stage of learning Chinese.
Keywords: cognition; expression of space; reference object; reference frame